RETRACTION OF: The Art to End All Arts - Herrie, Maja Bak; Dias, Tobias (The Nordic Journal of Aesthetics, 2025)
Retraction and removal notice: The manuscript published in The Nordic Journal of Aesthetics, Vol. 23, No. 46 (2013), pp. 63–77 has been retracted and removed as of May 13, 2025 due to plagiarism and scientific misconduct. The manuscript is no longer accessible through this site.